Multicriteria evaluaton of efficiency in fish processing - Dreimanis, Karlis; Indzere, Zane; Blumberga, Dagnija; Šerevičienė, Vaida (International Conference “Environmental Engineering”, 2020)
EU countries have agreed on GREEN DEAL and have committed to achieve carbon neutrality by 2050. Very important role for achieving the goal is playing production and manufacturing industry. This article is devoted to fish production industry, which is as subdivision of food production industry. During past decades the amount of fish caught has increased multiple times. Fishing industry nowadays is being strongly regulated and monitored by various institutions including. Which sets environmental legislation for controlling and improving industries impact (energy efficiency, pollution, waste) on the habitat and environment. For EU to make right decisions on how the member states could develop their fish production industry, it is necessary to have overall evaluation which includes the development opportunities. The efficiency of the fish production company characterizes the amount of resources used, as well as energy efficiency, water usage, the possibility to implement of circular economy, and other criteria which must be evaluated from the perspective if environmental, engineering, economic and social aspects. The fish production company analysis in this article are analysed using Data envelopement analysis (DEA) multicriteria analysis. First results show that fish manufacturers must pay attention to the technological processes in order to move towards carbon neutral society.
Keywords: fish production industry; data envelopement analysis; technological process